Using a Hybrid Pedagogical Method in Undergraduate Interior Design Education - Bhattacharjee, Suchismita (Design and Technology Education: An International Journal, 2019)
A flipped-classroom pedagogical method has been adopted by some educators over several past decades both knowingly and unknowingly. In this pedagogical method, the traditional classroom lecture and homework settings are flipped. Students are required to watch short video lectures as homework while the regular class sessions are devoted to in class activities. Flipped-classroom methods have been used as a pedagogical approach in different classroom environments from k-12 to college or university level class settings. There are several evidences of this pedagogical approach being adopted in both social science and pure science class settings. In this study, the author discusses the effectiveness of a flipped classroom method as a successful pedagogical approach for interior design students in achieving educational objectives. The author investigated a flipped classroom pedagogical method by adopting it in a sophomore level Interior Construction class. The choice to implement a flipped classroom method in this class was due to a rigid lecture and lab component which required the students to work on projects based on the lecture materials covered in the class. The course was taught by the same instructor covering similar content in three consecutive years; using a traditional pedagogical method, a flipped classroom pedagogical method and using a hybrid approach of traditional method and flipped classroom method. A one-way ANOVAresults of the student test scores suggested a significant effect of the pedagogical method on student performances for the three classes. Results suggest a flipped classroom as an effective way forward when combined with traditional method as adopted under the hybrid approach.